Behavior Study of Children’s Exposure to the Family Violence: Voices of Caregivers and Friends - Magar, Deena; Thakuri, Tika Bahadur (Shahid Kirti Multidisciplinary Journal, 2025)
Children’s Exposure to the family violence means child witnessing, hearing or being exposed to physical injuries, bruises or other indicators of violence. Family violence impact everyone who is exposed to it including the offenders, the victims and the children. This qualitative study expands common definitions of how children witness violence and its impacts on their behavioral changes through voices of 5 caregivers and 5 friends from the residential home located at Bhaktapur. In-depth interview and thematic analysis of narratives are used as data collection tools. Study focuses on incorporating case studies of children, systematic literature review and theories on the topic to explain the findings in more details and explore the research questions. The study has found that, children exposures to the family violence are impacted with fluctuating behaviors, adjustments and developments in life.